2015
DOI: 10.3390/e18010004
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study on Lexicon-based Ensemble Classification Sentiment Analysis

Abstract: Abstract:We propose a novel method for counting sentiment orientation that outperforms supervised learning approaches in time and memory complexity and is not statistically significantly different from them in accuracy. Our method consists of a novel approach to generating unigram, bigram and trigram lexicons. The proposed method, called frequentiment, is based on calculating the frequency of features (words) in the document and averaging their impact on the sentiment score as opposed to documents that do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…In the lexicon-based approach, one of the categories of lexicons approach is based on dictionary-based [62]- [65]. A set of hand-picked sentiment selected (features) are created and then expanded using a thesaurus or tools like WordNet [66]. Liu's lexicon [67] is a fully established example of this approach.…”
Section: Sentiment Analysismentioning
confidence: 99%
“…In the lexicon-based approach, one of the categories of lexicons approach is based on dictionary-based [62]- [65]. A set of hand-picked sentiment selected (features) are created and then expanded using a thesaurus or tools like WordNet [66]. Liu's lexicon [67] is a fully established example of this approach.…”
Section: Sentiment Analysismentioning
confidence: 99%
“…Firmino Alves et al (2013) give an insight of the main approaches for classifying sentiment polarity which are: machine learning, statistical approach, semantic approach and approach based on lexical analysis or thesaurus. Augustyniak, Łukasz et al (2015) describe that in the world of opinion mining predicting sentiment polarity from the text can be done by employing the specialists to manually classify the polarity, and can be done automatically or using both techniques. Hemalatha et al (2012) shows a very nice approach for pre-processing Twitter data following simple steps, and demonstrates how to prepare the data for training in machine learning technique.…”
Section: Sentiment Analysis On Twitter Datamentioning
confidence: 99%
“…Bandgar and Kumar (2015) using their research methodology illustrated how to create a windows application for real-time Twitter data for pre-processing of text data using available natural language processing resources like WordNet, SMS dictionary, Stanford dictionary. Augustyniak, Łukasz, et al (2015) proposed a new method called "frequentiment" that robotically evaluates sentiments (opinions) of the user from amazon reviews data set.…”
Section: Sentiment Analysis On Twitter Datamentioning
confidence: 99%
“…It has been found that the accuracy achieved from such lexicons outperforms other LB approaches. Augusttniak et al (2016) proposed a novel method frequentiment to count the sentiment orientation. The method was used to generate unigram, bigram and trigram lexicons.…”
Section: Lb Approachmentioning
confidence: 99%